The Golden Square and the Genesis of Iraqi Instability: Military Coups and Political Transformation in 1936 - Sarkawt Tawfeeq Sidiq (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2026)
The change in civil-military relations in Iraq during the period 1936-1937 marked the transformation of the military from a state defense institution into a political actor that played a direct role in the transfer of power. Although the 1936 military coup is recognized as the first coup in the Arab world, the factors driving this change and its impact on the development of Iraq’s political system still require comprehensive historical study. This research aims to analyze the main causes of the 1936-1937 military coups, evaluate their influence on the evolution of Iraq’s political system, and examine the relationship between domestic and external factors that shaped the success of military intervention. The research uses a qualitative historical approach through archival research, analyzing official British and Iraqi documents, memoirs, and various secondary historical sources. The results show that the weakening of civil institutions, the increasing politicization of the military, competition among political elites, and external interests created conditions that enabled the military to take on a political role. The 1936 coup not only changed the government but also legitimized military intervention as a mechanism of political change, thereby weakening constitutional government and altering the balance of power between civil and military authority. This research contributes to the understanding of the dynamics of civil-military relations and the origins of political instability in Iraq and developing countries in the Middle East.